Formulation for coating material - Abdul Rahman, Mohd Basyaruddin; Abd Ghani, Norani; Basri, Mahiran; Salleh, Abu Bakar; Raja Abdul Rahman, Raja Noor Zaliha (2011)
The present invention relates to a Solvent-free coating material and treating agents used as wood coating material as a protective agents. The wood coating material is used to provide a short a short period of time ultra-violetv(UV) radiation curing. Furthermore the coating material relates to an anticorrosion formulation and a method for forming a coated panel. This invention also provides a low valatility and high scratch resistance of coating for wooden surface.